Effects of old jute seeds on soil fertility and jute production (Journal of Biodiversity Conservation and Bioresource Management, 2020)
A field experiment was conducted to evaluate the effects of old jute seed powder (≥3 years old) on soil fertility and jute production using the high yielding variety of jute (Corchorus olitorius L.) O-9897 as the test plant. Six treatments of jute seed powder (JSP) and recommended dose of chemical fertilizers (RDF) with three replications were as T1: Control, T2: JSP 5 t/ha + ¼ RDF, T3: JSP 5 t/ha + ½ RDF, T4: JSP 5 t/ha + ¾ RDF, T5: RDF, and T6: JSP 5 t/ha. The growth and yield of jute were found to be the maximum for the treatment T4 (JSP+ ¾ RDF), where the plant height, base diameter, fiber yield and stick weight were increased 147, 85, 177, and 125%, respectively over the control. The highest contents of organic carbon, nitrogen, phosphorus, potassium, sulfur, calcium, and magnesium in soil were also observed for the treatment T4. The sole application of jute seed powder increased the growth and yield of jute as well as the contents of nutrients in soil compared to the control; however, inputs of the jute seed powder in combination with the chemical fertilizers showed better results in improving soil fertility and jute production.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 33-40